2017
DOI: 10.1039/c6me00077k
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the interplay of quantum interference and backbone rigidity on electronic transport in peptides: a step towards bio-inspired quantum interferometers

Abstract: Deposition and sharing rightsWhen the author accepts the licence to publish for a journal article, he/she retains certain rights concerning the deposition of the whole article. This table summarises how you may distribute the accepted manuscript and version of record of your article. Electron transfer in peptides provides an opportunity to mimic nature for applications in bio-inspired molecular electronics. However, quantum interference effects, which become significant at the molecular level, have yet to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 50 publications
(71 reference statements)
4
17
0
Order By: Relevance
“…The calculated conductance for both peptides was found to be remarkably similar, contrasting the approximate ten-fold difference in the electron transfer rate constants observed in the electrochemical study. 28 Similar results were also recently reported in helical peptides based on the same theoretical approach. 13 This suggests that different charge transfer mechanisms may be operating in these helical peptides, which cannot be determined using ballistic scattering transport simulations.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…The calculated conductance for both peptides was found to be remarkably similar, contrasting the approximate ten-fold difference in the electron transfer rate constants observed in the electrochemical study. 28 Similar results were also recently reported in helical peptides based on the same theoretical approach. 13 This suggests that different charge transfer mechanisms may be operating in these helical peptides, which cannot be determined using ballistic scattering transport simulations.…”
Section: Introductionsupporting
confidence: 83%
“…We and others have previously demonstrated that the addition of a tether linking the side-chains of peptides via Huisgen cycloaddition, [21][22][23] ring closing metathesis, [24][25][26][27] or lactamization, [28][29][30] xes the structural conformation into a well-dened helical geometry. The resulting decrease in backbone exibility leads to a reduction of torsional motion necessary for facile electron transfer through the peptide via a hopping mechanism, which in turn impacts the associated electron transfer dynamics and hence their electronic properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The component geminally disubstituted Aib (α-aminoisobutyric acid) residues of 3-8 promote formation of a common 3 10 -helical geometry, as demonstrated by molecular modelling and spectroscopic characterization. 16,28,29 Thus, as these peptides each share a similar well-defined backbone geometry, any disparity in the electron transfer kinetics can be directly correlated to the associated dynamic effects arising from the presence (or absence) of the side-bridge constraint. with the magnitude of this shift significantly higher than other conformation-dependent structures such as cis-trans cyclohexasilanes (110 mV), 31 placing it between the voltage drops across a germanium (300 mV-350 mV) and a silicon (600 mV-700 mV) p-n junction.…”
Section: Backbone Rigidity and Controllable Mechanistic Transitionmentioning
confidence: 99%
“…14 (3) An electrode-supported monolayer of peptides comprising a redox active probe for electrochemical measurements. This is a particularly versatile technique adopted by a broader research community (Kimura 1 , Kraatz 15 and our group 16 ). In the literature, the terminology referred to in the first instance is "electronic transport", while in the latter two it is commonly referred to as "electron transfer".…”
Section: Introductionmentioning
confidence: 99%